Liver sex dimorphism and zonation shaped by growth hormone - Becu, Damasia (2022)
In clinical medicine, the consideration of sex-specific differences in diagnosis and treatment of many diseases is gaining acceptance. In this context, sex differences in liver function and gene expression are important, although not highlighted in medical practice. In humans, significant sex differences in the bioavailability and clearance of drugs and other xenobiotics, as well as sex-biased proneness to different liver disorders, have been described. Sexually dimorphic gene expression of the liver depends mainly on growth hormone (GH) secretory patterns, and to a lesser extent on sex steroids. The brain is paramount in organizing GH pulses through synchronization of growth hormone–releasing hormone and somatostatin release and feedback responses (1), thus shaping liver sex dimorphism in accordance with the need for sex-specific steroid metabolism, and metabolic or even behavioral performance. High intermittent GH pulses are found in males, while females have a more constant secretory pattern in rodents; this pattern is found also in humans, although to a minor extent. This differential pulsatility is a key factor for the establishment and maintenance of sexual dimorphism in the transcription of liver genes (2-4). More than 1000 liver genes are sexually dimorphic, and of these approximately 90% are GH dependent (2). Sex differences in gene expression range from less than 2-fold to >1000-fold in the mouse, and this should alert to the need of considering sex as a variable when instrumenting different liver therapies, or administering drugs metabolized in a sex-specific manner.